2019
DOI: 10.1016/j.matcom.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Checking the quality of approximation of p-values in statistical tests for random number generators by using a three-level test

Abstract: Statistical tests of pseudorandom number generators (PRNGs) are applicable to any type of random number generators and are indispensable for evaluation. While several practical packages for statistical tests of randomness exist, they may suffer from a lack of reliability: for some tests, the amount of approximation error can be deemed significant. Reducing this error by finding a better approximation is necessary, but it generally requires an enormous amount of effort. In this paper, we introduce an experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The p-value uniformity test requires at least 55 samples. As mentioned before, it is remarked that passing the NIST SP 800-22 does not ensure a sequence to be truly random (Kim et al 2020;Fan et al 2014;Haramoto and Matsumoto 2019).…”
Section: Test Descriptionmentioning
confidence: 99%
“…The p-value uniformity test requires at least 55 samples. As mentioned before, it is remarked that passing the NIST SP 800-22 does not ensure a sequence to be truly random (Kim et al 2020;Fan et al 2014;Haramoto and Matsumoto 2019).…”
Section: Test Descriptionmentioning
confidence: 99%
“…The p-value uniformity test requires at least 55 samples. As mentioned before, it is remarked that passing the NIST SP 800-22 does not ensure a sequence to be truly random [21,22,23].…”
Section: Cumulative Sums Testmentioning
confidence: 99%
“…First, we consider the twolevel test for the following three one-level tests: the test for the Longest-Runof-Ones in a Block, the Overlapping Template Matching test, and the Linear Complexity test. Note that we apply a modification to the test for the Longest-Run-of-Ones in a Block to improve the approximation of p-values [3].…”
Section: Computing the Distributions Of P-values Of Some Statistical ...mentioning
confidence: 99%
“…Later, Pareschi et al [15] found a further good approximation value σ 2 2 = 0.05 • 0.95n/3.8. According to [3], we use σ 2 2 for variance in the following experiments.…”
Section: Monte Carlo Computation Of the Distributions Of P-valuesmentioning
confidence: 99%